3D image-based methods for investigating additive manufactured spinal implants (Transactions on Additive Manufacturing Meets Medicine, 2019)
Spinal fixation is a standard of care for patients who suffer from traumatic and chronic injuries that affect mobility and cause increased pain. New additive manufacturing (AM) technologies typically use mechanobiologic approaches that encourage fusion in the spine and increased healing for patients. A workflow has been developed to compare the differences between as-designed and as-manufactured parts that utilize 3D CT scanning, image processing software, and simulation of performance to understand the effect of deviations on devices. This preliminary workflow has been tested with a spine truss implant part and through direct comparison between simulations of as-designed versus as-manufactured geometries.